SIV Env RhmAbs + N-803 at ART initiation prolongs viral decay without disrupting reservoir establishment in SIV-infected infant macaques. - Omotayo Farinre; Tzoalli Anaya; Alexis C King; Kedan Endrias; Anne H Hébert; Alison L Hill; Sherrie Jean; Jennifer S Wood; Stephanie Ehnert; Shan Liang; Gregory M Laird; Rosemarie D Mason; et al. (PLoS Pathogens)
The latent viral reservoir remains the major barrier to HIV cure, placing the burden of strict adherence to antiretroviral therapy (ART) on people living with HIV to prevent recrudescence of viremia. For infants with perinatally acquired HIV, adherence is anticipated to be a lifelong need. In this study, we tested the hypothesis that administration of ART and viral Envelope-specific rhesus-derived IgG1 monoclonal antibodies (RhmAbs) with or without the IL-15 superagonist N-803 early in infection would limit viral reservoir establishment in SIV-infected infant rhesus macaques. Following initiation of ART at 1-2 weeks after oral SIVmac251 infection, we observed biphasic decay of viremia, with first phase decay significantly faster in the ART + SIV RhmAbs-treated group compared to controls that received only ART. In contrast, the addition of N-803 to ART + SIV RhmAbs significantly slowed both the first and second phase viral decay compared to the ART only group. Treatment with a single dose of N-803 resulted in increased frequency of Ki67 expressing NK, CD8+, and CD4+ T cells. Levels of intact SIV proviruses in CD4+ T cells from blood, lymph nodes, and rectum at week 48 of ART did not differ across groups. Similarly, the time to viral rebound following ART interruption was not impacted by the experimental treatments. These results support the concept that the rebound-competent viral reservoir is formed within days after infection and that targeting only productively infected cells for clearance near the time of ART initiation, even during acute infection, may be insufficient to limit reservoir establishment.